Twice-Exceptional Learners' Perspectives on Effective Learning Strategies. (October 2013) - Willard-Holt, Colleen; Weber, Jessica; Morrison, Kristen L.; Horgan, Julia
This mixed-methods study investigates the perspectives of twice-exceptional students on learning strategies that have been recommended for them in the literature. Have the strategies recommended in the literature been implemented? Do students perceive the strategies to be beneficial in helping them learn? Participants represented a broad range of coexisting exceptionalities and ranged in age from 10 to 23 years. While mainly qualitative, this study was informed by a survey adapted from the Possibilities for Learning survey. Qualitative in-depth interviews provided rich descriptions of which learning strategies were facilitators and barriers. Findings indicated that participants perceived that their overall school experiences failed to assist them in learning to their potential, although they were able to use their strengths to circumvent their weaknesses. Implications for teachers included allowing twice-exceptional learners more ownership over their learning and more choice and flexibility in topic, method of learning, assessment, pace, and implementation of group collaboration.